Information sources for opinion leaders in the field of production and marketing of marjoram (Origanum majorana) in some villages of Minya Governorate - Aly, AlaaEl-Deen Aly Mohamed; Elsheref, Hamdy Mohamed Moawud; Osman, Nazek Samir Mahmoud (Journal of agricultural, environmental and veterinary sciences, 2022)
The research aimed to determine the sources of information of opinion leaders in the field of production and marketing of the marjoram crop, as well as to determine the correlation between the degree of use of the information sources of the opinion leaders surveyed for technical recommendations for the production and marketing of the marjoram crop and the independent variables studied, determining the percentage of the contribution of the studied independent variables in explaining the total variance of information sources. Opinion leaders in the field of marjoram production and marketing, as well as identifying the production and marketing obstacles of marjoram from the opinion leaders surveyed point of view. The research was conducted in Minya Governorate, as it is one of the largest governorates in terms of the area cultivated with marjoram, and the three largest centers were selected in terms of the area cultivated with the marjoram crop. The previous criterion, for the first two phases of the study, which is identifying and discovering opinion leaders from among the farmers, and also the second phase, which is defining the sources of opinion leaders’ information. The sample size reached 108 opinion leaders from the nine villages. These leaders were identified and discovered by the sociometric method. All the farmers were asked to mention the names of the farmers who specialize in the production and marketing of the marjoram crop and who turn to them for advice and advice in the field of producing and marketing marjoram in question. The data for this research was collected through a questionnaire form in the personal interview with the respondents, which had previously been prepared and reviewed, and after it became valid for data collection to achieve the objectives of the research. The multiple stepwise ascending correlation and regression analysis model (Step Wise), the arithmetic mean, the standard deviation, in addition to the tabular display with frequencies and percentages in displaying the results. The most important search results were: 1- One of the most important sources of information that opinion leaders surveyed resort to in the field of marjoram production and marketing is personal experience, followed by agricultural guidance in the field of marjoram production, while personal experience is considered, followed by family and relatives in the field of marjoram crop marketing. 2- It was found that there is a significant relationship between the degree of respondents’ use of marjoram production information sources and the following independent variables: average production acre, educational status, openness to the outside world, renewal, age, and it was found that there is a significant relationship between the degree of respondents’ use of sources of information. Marketing information for the marjoram crop and between the following independent variables: the size of the agricultural holding, the size of the holding planted with marjoram, the average acre production, openness to the outside world, renewal, age. 3- The three studied variables contributed to the overall variance that explains the information sources of the polled opinion leaders in the field of marjoram crop production, and their combined contribution rate was 46.0%, 39.1% of which was attributed to the variable of renewal, 4.0% to the variable of educational status, and 2.9% to the variable of openness on the outside world. Only two independent variables contributed to the overall variance that explains the information sources of the respondents in the field of marketing the marjoram crop, and their combined contribution was 17.8%, 12.3% of which was attributed to the variable size of the cultivated holding of marjoram, and 5.5% to the average acre production variable.average acre production. 4- One of the most important productive obstacles to the marjoram crop were the high value of the rent of agricultural land, the high prices of seedlings, the high wages of agricultural labor, as for the marketing obstacles for the marjoram crop, they were represented in: the monopoly of major traders and their interference in determining the price of the crop, the farmers’ suffering in collecting the selling price of the crop The lack of juicers in the area to extract the oil.